Internet traffic control with applications in multimedia systems - Cheng, Chen (2010)
Multimedia applications with various Quality of Service (QoS) requirements have posed great challenges to the "flat" service of the Internet. In this thesis, we shall present several results to enhance the source adaptation and control of multimedia traffic. Specifically, a source adaptation framework and two pricing systems are designed. Our schemes do not require significant modifications to the architecture of the Internet. Thus, they can be readily deployed over the current Internet.